2020
DOI: 10.1111/odi.13752
|View full text |Cite
|
Sign up to set email alerts
|

Oil pulling to relieve medication‐induced xerostomia: A randomized, single‐blind, crossover trial

Abstract: Objectives: To determine the subjective effectiveness of oilpulling on medicationinduced xerostomia with regard to symptom relief, quality of life, taste, mucosal moisture and oral parameters. Materials and Methods:In a randomized, single-blind, crossover trial in participants with medication-induced xerostomia (n = 26; mean age 64.71 (standard deviation (SD) 15.60) years), we investigated oilpulling efficacy (sunflower oil) versus mineral water after one-week use. Xerostomic burden (visual analogue scale, VAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The cut‐off value of 4 cm on the VAS was chosen by the authors when defining these inclusion groups because the subjective dry mouth group should represent people with a relevant subjective burden; those with a very low burden should be left out. Similar considerations have already been published by this group for subjective dry mouth inclusion criteria for other studies [40]. According to our sample size calculation (described below), each of those inclusion groups comprised N = 30 participants.…”
Section: Methodsmentioning
confidence: 89%
“…The cut‐off value of 4 cm on the VAS was chosen by the authors when defining these inclusion groups because the subjective dry mouth group should represent people with a relevant subjective burden; those with a very low burden should be left out. Similar considerations have already been published by this group for subjective dry mouth inclusion criteria for other studies [40]. According to our sample size calculation (described below), each of those inclusion groups comprised N = 30 participants.…”
Section: Methodsmentioning
confidence: 89%
“…Table 1 summarized the characteristics of the included trial studies. From the 25 trials involving 1184 participants, the majority were conducted in India (n = 19), 11,13,14,18,20,[39][40][41][42][43][44][45][46][47][48][49][50][51] whereas the remaining trials were implemented in Turkey, 43 Egypt, 52 Germany, 21 Malaysia, 53 and two with no reported region of study. 54,55 The number of participants included in each trial was comparatively small, ranging between 8 to 75.…”
Section: Participantmentioning
confidence: 99%
“…The majority (17 out of 25) of the trials included participants with no reported oral health issues. 11,14,18,20,[39][40][41][44][45][46][50][51][52][53][54]56,57 Of the remaining eight trials, six trials recruited participants with mild to moderate gingivitis, 13,42,[47][48][49]55 one trial included participants with Xerostomia, 21 and one trial included post-dental operative adults. 43 Trials comprised of mainly adults.…”
Section: Participantmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these synthetic compounds also showed some adverse effects. Natural or herbal extracts may be alternative options to reduce oral infection with few adverse effects in the bacterial reduction (Sookkhee et al, 2001), inhibition of plaque development (Amith et al, 2007;Asokan et al, 2009), prevention of caries and gingivitis (An et al, 2008;Peedikayil et al, 2015), relief of dry mouth (Ludwar et al, 2022), reduction of bad breath (Asokan et al, 2011a), and inhibition of fungal growth (Ogbolu et al, 2007;Owittayakul et al, 2018). One of these options was vegetable oil pulling for promoting oral hygiene (Shanbhag, 2017).…”
Section: Introductionmentioning
confidence: 99%